MÍDIAS DIGITAIS SOCIAIS NO AUXÍLIO AO EAD: As Novas Tecnologias da Informação e da Comunicação como processo facilitador na relação de ensino-aprendizagem - Calipo, Valeria (2013)
At the present study, we investigated whether the educational institutions adoption of resources and available tools in the social digital media (which allow both synchronized and asynchronized communication) stimulates communication for more interactivity, dialogicity and collaboration between the involved agents in the teaching and learning process via distance education. In order to do so, we checked how students on distance education react to new possibilities offered with the advent of new technologies of information and communication- NTICs. Our study focuses in undergraduate students who were, at the moment of the research, taking the second two months of the following Technological Courses: Marketing, Logistics, Human Resources and Management to Distance Education, from both Anhanguera and Metodista universities, at São Caetano do Sul and Mauá centres. In the sample, we have opted the non-probabilistical model of intention sort, adopting the criterion that the selected students knew both resources and tools being used in their institutions media. As the measurement instrument, we applied a Likert type quiz, composed by 7 dimensions and 32 assertions, besides the technique of focal group interview, numbering 5 meetings. We historically brought some points about the movement of the new technologies, noticeably the digital ones, as well as the distance education, from last centuries to the present days. Furthermore, we made the effort to understand how much the governmental actions have supported the technological transformations which have direct and indirect impact on the educational aspects. Another discussed topic was the Society of Knowledge, which has an extremely important role for the development and advance of the NTICs. The discussions for the data analyses were oriented by Habermas Theory of Communicative Action, which helped understand and indicate the importance of the concepts about the world of Life and the world of System, within the present reality of distance education and NTICs. The results have pointed that the students in both universities (married, parents, people who want to make use of their studies in order to have a better career step, have Internet home access, as well as at work and university) are aware of and use the Social Digital Media offered by their universities in order to communicate with their university mates and professors, but they interact in a better way with the market-offered tools, available on the internet. They also significantly make use of the e-mail as a means of communication among university mates. The study has also observed that the research group belongs to a generation of digital immigrants that adapted and use the universities offered tools reasonably well. However, it has indicated that the resources and digital tools, which may make the communicational process easier, within educational institutions, they are still limited in relation to the possibilities offered by the new digital technologies on the market. For most of them, the Social Digital Media are notable and make the communicative process easier within the teaching and learning relation. Nevertheless, they point to the fact that the dialogue between professors or tutors and students could be more dynamic if there were more on-line interaction. The study has evidenced that the social digital media and their tools, offered by the market and used outside the distance education network, for being more interactive and intuitive and being linked to a more informal environment, allow more collaboration and faster communication than the ones seen at the distance education network.